Ecological Interpretation: Analysis of Qur'anic Verses on the Environment from a Contemporary Interpretation Perspective - Gani, Fahima; Amaliya, Nila Khoiru; Dardirie, Achmad (Manunggal Halim Jaya, 2025)
This study aims to analyze the verses of the Qur'an related to the environment through the perspective of contemporary interpretation. The study focuses on how the ecological messages in the Qur'an provide an ethical-theological foundation for humans as khalīfah to maintain the balance of nature. The research method used is qualitative-descriptive with a library research approach, reviewing classical and contemporary interpretation literature, and the latest scientific articles. The results of the study show that verses such as QS. Al-A'raf (7): 56–57, QS. Ar-Rum (30): 41, and QS. Al-Baqarah (2): 164 provides a comprehensive picture of the importance of maintaining ecosystem sustainability and the impact of environmental damage caused by human actions. The analysis of ecological interpretation confirms that rain, plants, and the balance of nature are manifestations of God's grace and human ethical-spiritual responsibilities. Thus, ecological interpretation can be used as a new paradigm in environmentally aware Islamic education and an Islamic contribution to solving the global ecological crisis.